Cultural Differences And Semiotic Variations In English And Persian: A Study Of Translation Problems - Sharififar, Masoud (2007)
This study aims to investigate the cultural differences between English and Persian which may be problematic in translating from English into Persian. The study aims also to investigate the way cultural elements are dealt with in the selected corpora and to check whether the procedures proposed by Newmark, Vinay and Darbelnet and Mollanazar are sufficient and adequate for the translation of cultural elements from English into Persian. Two dramas, A Streetcar named Desire by T. Williams and The Pilgrim’s Progress by J. Bunyan and one novel, The Great Gatsby by S.Fitzgerald and their corresponding translated Persian versions are analyzed. This study is also narrowed down to only non-verbal, religious and social cultural elements. This investigation uses Newmark’s theory of translation (1998). The findings obtained from the textual analyses of the related data show that the transfer of social cultural elements is the least problematic and of non-verbal elements including acoustic and linguistic signs as well as religious elements are the most problematic for the translators.